2021
DOI: 10.3390/ph14100954
|View full text |Cite
|
Sign up to set email alerts
|

A Drug Repurposing Approach for Antimalarials Interfering with SARS-CoV-2 Spike Protein Receptor Binding Domain (RBD) and Human Angiotensin-Converting Enzyme 2 (ACE2)

Abstract: Host cell invasion by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is mediated by the interaction of the viral spike protein (S) with human angiotensin-converting enzyme 2 (ACE2) through the receptor-binding domain (RBD). In this work, computational and experimental techniques were combined to screen antimalarial compounds from different chemical classes, with the aim of identifying small molecules interfering with the RBD-ACE2 interaction and, consequently, with cell invasion. Docking studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 64 publications
1
22
0
Order By: Relevance
“…R f (CH 2 Cl 2 ) 0.5; δ H (600 MHz, CDCl 3 ) 8.82 (1H, d, J = 4.9 Hz, H-2), 8.09 (1H, d, J = 2.4 Hz, H-8), 8.01 (1H, d, J 9.3, H-5), 7.49 (1H, dd, J 2.4 and 9.3, H-6) 7.12 (1H, d, J 4.9, H-3) ppm; δ C (150 MHz, CDCl 3 ) 150.9, 149.1, 146.8, 136.9, 127.9, 123.8, 119.9, 108.7 ppm. The spectral characteristics are consistent with those of 2 in the literature [20].…”
Section: Chemistrysupporting
confidence: 89%
See 1 more Smart Citation
“…R f (CH 2 Cl 2 ) 0.5; δ H (600 MHz, CDCl 3 ) 8.82 (1H, d, J = 4.9 Hz, H-2), 8.09 (1H, d, J = 2.4 Hz, H-8), 8.01 (1H, d, J 9.3, H-5), 7.49 (1H, dd, J 2.4 and 9.3, H-6) 7.12 (1H, d, J 4.9, H-3) ppm; δ C (150 MHz, CDCl 3 ) 150.9, 149.1, 146.8, 136.9, 127.9, 123.8, 119.9, 108.7 ppm. The spectral characteristics are consistent with those of 2 in the literature [20].…”
Section: Chemistrysupporting
confidence: 89%
“…BLI also provides the calculation of kinetic parameters, such as association rate (k on ) and dissociation rate (k dis ), as well as of dissociation constant (K D ). This technique was recently adopted to screen RBD ligands in combination with virtual screening [20]. As shown in Figure S11 of the Supplementary Materials, the results of BLI conducted on synthesized compound demonstrated a poor affinity with RBD spike of SARS-CoV-2 (delta variant), with a modest correlation value.…”
Section: Resultsmentioning
confidence: 99%
“…(2020) demonstrated that withanone efficiently inhibited the interaction between ACE2R and RBD in vitro , with an IC 50 of 0.33 ng/mL [ 62 ]. Two other compounds structurally close to withanolide F, peimine and artemisone, also exhibited similar activities [ 64 , 65 ]. In a study by Wang et al, Peimine inhibited variants of SARS‐CoV‐2 infection in furin‐overexpressing cells with an IC 50 of 0.4 μM against wild-type, alpha, and beta variants.…”
Section: Resultsmentioning
confidence: 99%
“…Molavi et al repurposed 1760 FDA-approved drugs to Mpro and RdRp, and Rajpoot et al repurposed 291 drugs to Mpro and PLpro. More similar works include refs , , , , , , , , , , and .…”
Section: Methods and Approachesmentioning
confidence: 97%
“… 1146 repurposed 291 drugs to Mpro and PLpro. More similar works include refs ( 599 , 609 , 622 , 624 , 628 , 632 , 637 , 838 , 875 , 889 , and 1147 1173 ).…”
Section: Methods and Approachesmentioning
confidence: 99%